Antimicrobial peptide in polymethylmethacrylate bone cement as a prophylaxis of infectious complications in orthopedics-an experiment in a murine model - Melicherčík, Pavel; Kotaška, Karel; Jahoda, David; Landor, Ivan; Čeřovský, Václav (Folia microbiologica, 2022)
Polymethylmethacrylate (PMMA) bone cement mixed with antibiotics is used in orthopedic surgery to cope with implant-related infections which are typically associated with the formation of bacterial biofilms. Taking into account the growing bacterial resistance to current antibiotics, we examined here the efficacy of a selected antimicrobial peptide (AMP) mixed into the bone cement to inhibit bacterial adhesion and the consequent biofilm formation on its surface. In particular, we followed the formation of bacterial biofilms of methicillin-resistant Staphylococcus aureus (MRSA) on implants made from PMMA bone cement loaded with AMP composed of 12 amino acid residues. This was evaluated by CFU counting of bacteria released by sonication from the biofilms formed on their surfaces after these implants were retrieved from the infected murine femoral canals. The AMP loaded in these model implants prevented adhesion of MRSA and the subsequent formation of MRSA biofilm on the surfaces of more than 80% of these implants, whereas biofilms did form on control implants made from the plain cement. The results of our experiments performed in the murine femoral canal indicate the potential for this murine osteomyelitis model to mimic actual operations in orthopedics.
Keywords: Antimicrobial peptide; modely nemocí na zvířatech; Implant-related infections; Bacterial biofilm; Antimicrobial Peptides; antimikrobiální peptidy; Murine model; Methicillin-Resistant Staphylococcus aureus; antibakteriální látky; zvířata; myši; Polymethylmethacrylate bone cement; aminokyseliny; Mice; kostní cementy; Amino Acids; methicilin rezistentní Staphylococcus aureus; ortopedické výkony; Anti-Bacterial Agents; biofilmy; polymethylmethakrylát; PMMA implants; Bone Cements; Orthopedic Procedures; Polymethyl Methacrylate; Animals; Disease Models, Animal; Biofilms